Astro-tourism in Portugal’s rural areas - Rodrigues, Áurea (2022)
This chapter unfolds as a case study in Portugal about The Dark Sky® Network, which includes the Dark Sky® Alqueva, the Dark Sky® Schist Villages and the Dark Sky® Valley of Tua destinations. The study focuses on these exquisite locations, which have achieved international recognition for their original tourism product: astro-tourism. The present work analyses the implementation and development of this process and present progress of astro-tourism locations, as well as highlight the relevance of working through networks. This case study methodology is based on the analysis of documents from various sources, semi-structured interviews, and participant observation. The findings disclose details of how to function within a networking system. Astro-tourism opens a door for a potential niche tourism segment with unique characteristics and capacities, aiming to develop rural destinations. This chapter advances recommendations which are relevant for the successful implementation of this niche tourism product in rural destinations.